Distribution and Stability of Organic Carbon in Soil Aggregate External and Internal Layers under Three Different Land‐Use Systems. Issue 5 (20th September 2013) - Fan, Ruqin; Yang, Xueming; Drury, Craig F.; Guo, Xiaobin; Zhang, Xiaoping
Abstract : Soil aggregates may protect organic matter from mineralization; however, there is a lack of knowledge about the stability and structural features of soil organic carbon (SOC) in aggregate external layers and the internal layers. The amount and characteristics of SOC in external and internal layers of soil dry‐sieved aggregates from three land use systems (woodlot, grassland, and arable land) were studied using an aerobic incubation. Structural features of SOC and hot water‐extractable C, prior‐ and post‐incubations, were investigated using Fourier transform mid‐infrared spectroscopy. Soil organic C concentrations were 11.1 and 6.8% greater in the internal layers than in external layers of soil aggregates in woodlot and grassland systems, respectively, while there was no difference between the aggregate layers in arable soil. The CO2 –C evolved during the aerobic incubation was significantly greater from aggregate external layers than from internal layers under all three land use systems. The content of aliphatic‐C was significantly greater in aggregate external layers than in internal layers under all three land use systems, while the content of aromatic‐C was greater in aggregate internal layers than in external layers for the woodlot and grassland systems only. The SOC in aggregate internal layers had a longer half‐life, a greater slow‐C pool and a smaller active‐C pool than the SOC in aggregate external layers. The SOC is characterized with higher aromatization and stability in aggregate internal layers than in aggregate external layers. The aggregates are better developed and provide strong protection for SOC in the native woodlot and grassland systems but this protection was not evolved in arable land.